2017
DOI: 10.1140/epjd/e2017-70740-7
|View full text |Cite
|
Sign up to set email alerts
|

Rotationally inelastic cross sections, rates and cooling times for para-H2 +, ortho-D2 + and HD+ in cold helium gas

Abstract: Abstract. In the present work we discuss the dynamical processes guiding the relaxation of the internal rotational energy of three diatomic ions, the para-H + 2 , the ortho-D + 2 and the HD + in collision with He atoms. The state-changing cross sections and rates for these Molecular Hydrogen Ions (MHIs) are obtained from Close Coupling quantum dynamics calculations and the decay times into their respective ground states are computed by further solving the relevant time-evolution equations. The comparison of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…A more extended discussion of the variety of inelastic cross sections in the low temperature region which we have obtained for the present systems has been presented in a separate publications [20,26]. We therefore refer the interested reader to it for further details.…”
Section: Ho-rr and Va Rovibrational State-changing Cross Sectionsmentioning
confidence: 88%
“…A more extended discussion of the variety of inelastic cross sections in the low temperature region which we have obtained for the present systems has been presented in a separate publications [20,26]. We therefore refer the interested reader to it for further details.…”
Section: Ho-rr and Va Rovibrational State-changing Cross Sectionsmentioning
confidence: 88%
“…For para-H 2 + we performed exact scattering calculations, including the electron-spin-rotation coupling s e · N. We repeated them by treating the molecule as a pseudo-1 system (i.e., ignoring electron spin and therefore ignoring the spinrotation coupling). We compared the cross sections for both cases (summed over the spin states in the exact treatment) and found that they agree within 20%, mostly within 10% [46]. Thus, the spin dependence of the cross sections can be neglected for the present purpose.…”
Section: The H 2 + Casementioning
confidence: 89%
“…Here we limit ourselves to MHIs in the ground vibrational level v = 0. The detailed features of the potential are analyzed elsewhere [46]. Multipolar coefficients up to λ = 20 were included.…”
Section: B Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Schaupp et al [1] reported an investigation of the correlated electron-nuclear dynamics in a dissociating model system, using both classical and quantum mechanical methodologies. A study of the relaxation dynamics of the internal rotational energy of the diatomic ions para-H + 2 , orto-D + 2 , and HD + in collision with cold He atoms has been presented by Hernández Vera et al [2]. A comprehensive analysis of the vibrational structure of the CO 2 system applying a polyad-preserving algebraic approach was presented and discussed by Bermudez-Montaña et al [3].…”
Section: Progress In Molecular Dynamicsmentioning
confidence: 99%